REFORMS IN THE FIGHT AGAINST CORRUPTION IN UZBEKISTAN: THEORY AND PRACTICE - Niyozova Salomat Saparovna (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to analyze the reforms and practical measures undertaken in combating corruption in the Republic of Uzbekistan, with a focus on both theoretical underpinnings and institutional applications. Method: Utilizing a qualitative-descriptive approach, the research draws from national legal documents, policy frameworks, and a critical discourse analysis of the President’s speech at the National Anti-Corruption Council meeting on March 5, 2025. Results: The findings reveal significant progress in institutionalizing anti-corruption mechanisms through legal reforms, digitalization efforts, performance-based governance, and enhanced inter-agency cooperation. The role of civic participation and political will emerges as a cornerstone in reinforcing transparency and public accountability. A comparative analysis with global best practices highlights both achievements and persisting challenges, particularly in public oversight and cultural attitudes toward corruption. Novelty: This article provides a timely and in-depth examination of Uzbekistan’s evolving anti-corruption architecture, uniquely contextualized through the lens of presidential directives and national strategic goals. It contributes new insights into how transitional economies can leverage legal and digital innovations to strengthen ethical governance and institutional resilience.